"Manni líður eins og maður sé alltaf að stara í ginið á ljóninu": Viðhorf ungra kvenna til barneigna - Símonardóttir, Sunna Kristín; Guðmundsdóttir, Hlédís Maren (MISC, 2025)
Declining birth rates in Western countries can be attributed to changes in attitudes towards childbearing as well as social factors such as increased prosperity, education, increased gender equality and changes in life values and goals. Iceland now follows similar fertility trends as the other Nordic countries. Existing research is limited, underlining the importance of broad context research of birth rates and fertility behaviour. The purpose of this study is to further our understanding of how attitudes towards childbearing are shaped by prevailing ideas about parenthood, people’s social conditions, gendered reality, and family policy. In the study, we employ focus groups and individual interviews with women aged 25-30 to analyse young women’s attitudes towards childbearing. Our analysis sheds light on young women’s view of motherhood as distressing and likely to negatively impact their social position. Although the interviewees perceive cracks in the facade of the egalitarian society, when it comes to the inequal responsibilities of mothers and fathers, they do not question the ideology of individualism and intensive mothering that characterizes modern parenthood. Findings suggest that young women struggle to envision how they can meet the demands of motherhood in a society characterized by materialism, individualism, and impending climate disaster.